2018
DOI: 10.2147/ijn.s166000
|View full text |Cite
|
Sign up to set email alerts
|

Nano-therapeutic cancer immunotherapy using hyperthermia-induced heat shock proteins: insights from mathematical modeling

Abstract: BackgroundNano-therapeutic utilizing hyperthermia therapy in combination with chemotherapy, surgery, and radiation is known to treat various types of cancer. These cancer treatments normally focus on reducing tumor burden. Nevertheless, it is still challenging to confine adequate thermal energy in a tumor and obtain a complete tumor ablation to avoid recurrence and metastasis while leaving normal tissues unaffected. Consequently, it is critical to attain an alternative tumor-killing mechanism to circumvent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…They found that the maximum extracellular HSP synthesis was at 43°C, so was the maximum modulatory effect for tumor regression and decreased metastasis. When the temperature was further increased, HSP synthesis decreased, and the immune modulatory effect of hyperthermia was also downregulated (48). Whereas, through bioinformatic approach, Duzgun et al identified a series of molecules that determine the thermoresistance and immunogenic cell death in thermotherapy through estimating the percentage of the two kinds of denatured proteins.…”
Section: Hsps Are Among the Most Important Damps Induced By Hyperthermiamentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the maximum extracellular HSP synthesis was at 43°C, so was the maximum modulatory effect for tumor regression and decreased metastasis. When the temperature was further increased, HSP synthesis decreased, and the immune modulatory effect of hyperthermia was also downregulated (48). Whereas, through bioinformatic approach, Duzgun et al identified a series of molecules that determine the thermoresistance and immunogenic cell death in thermotherapy through estimating the percentage of the two kinds of denatured proteins.…”
Section: Hsps Are Among the Most Important Damps Induced By Hyperthermiamentioning
confidence: 99%
“…They found that the maximum extracellular HSP synthesis was at 43°C, so was the maximum modulatory effect for tumor regression and decreased metastasis. When the temperature was further increased, HSP synthesis decreased, and the immune modulatory effect of hyperthermia was also downregulated ( 48 ). Whereas, through bioinformatic approach, Duzgun et al.…”
Section: Hyperthermia Is a Strong Icd Inducermentioning
confidence: 99%
“…This effect of combination therapy was also validated in an in vivo mouse prostate cancer model [ 172 ]. Hyperthermia also increased extracellular Hsps during tumor necrosis, which induced immunity against tumor cells [ 173 ]. However, some studies reported the roles of Hsp70 in radioresistance and Hsp72 in etoposide-induced apoptosis resistance [ 174 , 175 ].…”
Section: Molecular Mechanisms Of Immunogenicity By Hyperthermiamentioning
confidence: 99%
“…blood perfusion, electrical conductivity, and the cell death model, in the prediction of RFA zone size in the liver. Lin et al [34] utilized the three-state cell death model to predict the optimum temperature and exposure time that generates the maximum heat shock protein and reduces metastasis in nontherapeutic cancer immunotherapy by using hyperthermia.…”
Section: Introductionmentioning
confidence: 99%